Risk factors for repeated recurrence of cerebral aneurysms treated with endovascular embolization - Han, Yong-Feng; Jiang, Peng; Tian, Zhong-Bin; Chen, Xi-Heng; Liu, Jian; Wu, Zhong-Xue; Gao, Bu-Lang; Ren, Chun-Feng (Frontiers in Neurology, 2022)
Purpose: To explore the risk factors of recurrence after second endovascular embolization of recurrent aneurysms and the characteristics of recurrent refractory aneurysms to help clinical decision making. Materials and methods：Forty-nine patients with recurrent aneurysms who underwent repeated embolization were retrospectively enrolled and divided into the recurrent and non-recurrent group. The risk factors of recurrence, complications and follow-up results of repeated embolization and characteristics of recurrent refractory aneurysms were analyzed. Results: Among the 49 patients with the second embolization, five were lost to follow-up, nine recurred, and 35 did not. Univariate analysis showed aneurysm size (P=0.022), aneurysm classification (P=0.014), and Raymond-Roy grade after the second embolization (P=0.001) were statistically different between the two groups. Multivariate analysis demonstrated the Raymond-Roy grade as an independent risk factor for recurrence of aneurysms after the second embolization (P = 0.042). The complication rate after second embolization was 4%. There were five recurrent refractory aneurysms with an average aneurysm size of 23.17±10.45mm, including three giant aneurysms and two large aneurysms. To achieve complete or near-complete embolization of the recurrent refractory aneurysms, multiple treatment approaches were needed with multiple stents or flow diverting devices. Conclusion: Aneurysm occlusion status after the second embolization is an independent risk factor for recurrence of intracranial aneurysms. Compared with the near-complete occlusion, complete occlusion can significantly reduce the risk of recurrence after second embolization. In order to achieve complete or near-complete occlusion, recurrent refractory aneurysms need multiple treatment with the use of multiple stents or flow diverting devices.